Molecular Characterization of KPC-2-Producing Enterobacter cloacae Complex Isolates from Cali, Colombia - Aura Falco; Daniela Guerrero; Isabella García; Adriana Correa; Sandra Rivera; María Beatriz Olaya; Carlos Aranaga (MDPI AG, 2021)
The Enterobacter cloacae complex is an emerging opportunistic pathogen whose increased resistance to carbapenems is considered a public health problem. This is due to the loss of efficacy of beta-lactam antibiotics, which are used as the first treatment option in the management of infections caused by Gram-negative bacteria. The objective of this study was to perform the molecular characterization of 28 isolates of the E. cloacae complex resistant to cephalosporins and carbapenems isolated between 2011 and 2018 from five hospitals located in the municipality of Santiago de Cali, Colombia. Molecular detection of blaKPC, blaVIM, blaNDM and blaOXA-48-like genes was performed on these isolates and the genetic relationship between the isolates was assessed using multilocus sequence typing (MLST). Forty-three percent of the isolates carried the blaKPC-2 gene variant. MLST showed high genetic diversity among isolates, the most frequent being the sequence type ST510 with a frequency of 50%. The identification of the genes involved in carbapenem resistance and dispersing genotypes is an important step toward the development of effective prevention and epidemiological surveillance strategies in Colombian hospitals.